"The fabrications of Nasr Abu Zeid in his book "Imam Shafi’i and the establishment of the middle ideology - Bani Salama, ‏​‏​‏​​‏​‏​​‏​‏​‏​‏​‏​‏ Hossam El Din Mohamed (Journal of Islamic Sciences, 2018)
In this paper, I presented the author’s approach to questioning the origins of religion, especially the Sunnah of the Prophet, and how he relied on distant interpretations sometimes and on the blatant lies sometimes other; To prove his secular ideas, accusing in all this Imam Shafi’i God’s mercy that he was the first to expand the authority of texts and narrow the circle of reason. I have talked about the resemblance raised by the writer about the Koran and Sunnah, and about Imam Shafi’i God’s mercy, and echoed with clear evidence and clear evidence, thank God.